(untitled) - Didion, Joan (New York, 1987)
The book describes a place in which two profoundly different cultures co-exist and where the myths of Cuban exile have not only become the everyday stuff of local politics, but have spread out from Miami to the White House and beyond, to include the Bay of Pigs, the assassination of John F. Kennedy, the Watergate burglary and the finanting of the Nicaraguan Contras...
Keywords: Cuban american,Miami ( fla. ); Florida,Miami,Social conditions